Pembelajaran Emosi Melalui Flashcard Pada Anak Usia Dini Di TKIT Al-Fityan Gowa - Amirah Aminanty Agussalim; Astiti Tenriawaru Ahmad; Alviyuniasticha Alviyuniasticha IPRH; Anggun Amalia; Dearnie Regina Lestari; Fauziah Asnur (Universitas Negeri Makassar, 2023)
Understanding emotions has a major influence on children's socio-emotional development processes. Interventions need to be carried out to help children improve their emotional understanding so that their socio-emotional skills can develop better. This service is carried out to help young children recognize the types of emotions so they can understand and express them appropriately. The method used is service learning. The program is implemented in the form of providing emotional flash cards to help children identify and recognize emotions.The pre-test and post-test in this study were a list of emotion words that children needed to express. The effectiveness of the method can be seen from the difference in pre-test and post-test results. The results of the measurements show that emotion flash cards are very helpful and effective in understanding young children about emotions and have an impact on their socio-emotional development.